Antagomir-mediated suppression of microRNA-134 reduces kainic acid-induced seizures in immature mice - Campbell, Aoife (Sci Rep, 2021)
MicroRNAs are short non-coding RNAs that negatively regulate protein levels and perform important roles in establishing and maintaining neuronal network function. Previous studies in adult rodents have detected upregulation of microRNA-134 after prolonged seizures (status epilepticus) and demonstrated that silencing microRNA-134 using antisense oligonucleotides, termed antagomirs, has potent and long-lasting seizure-suppressive effects. Here we investigated whether targeting microRNA-134 can reduce or delay acute seizures in the immature brain. Status epilepticus was induced in 21 day-old (P21) male mice by systemic injection of 5 mg/kg kainic acid. This triggered prolonged electrographic seizures and select bilateral neuronal death within the CA3 subfield of the hippocampus. Expression of microRNA-134 and functional loading to Argonaute-2 was not significantly changed in the hippocampus after seizures in the model. Nevertheless, when levels of microRNA-134 were reduced by prior intracerebroventricular injection of an antagomir, kainic acid-induced seizures were delayed and less severe and mice displayed reduced neuronal death in the hippocampus. These studies demonstrate targeting microRNA-134 may have therapeutic applications for the treatment of seizures in children.